Good Corporate Governance (GCG) and Islamic Social Reporting (ISR): A bibliometric approach - Krismaya, Sinta; Ulum, Ihyaul; Oktavendi, Tri Wahyu; Afrizal, Faris; Mawardi, Fahmi Dwi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This study aims to visualize the topics of Good Corporate Governance and Islamic Social Reporting from previous studies to provide opportunities for further, more diverse research.Design/Methodology/Approach: This study employed a bibliometric approach study in the field of Good Corporate Governance and Islamic Social Reporting published in journals indexed by Scopus, SINTA, Emerald Insight, DOAJ, Research Gate, Science Direct, Garuda, and Google Scholar.Research findings: Research in the field of Good Corporate Governance and Islamic Social Reporting was carried out in 2010-2022, and authors from Indonesia wrote 398 articles. These findings identify publication metadata converted into visualizations in the fields of science, not only economics but also arts, humanities, and psychology, which have not been widely researched. Hence, they could be interesting topics for future research.Theoretical contribution/Originality: This paper is one of the articles that provides a better understanding of Good Corporate Governance and Islamic Social Reporting as a research topic. It examines its evolution in an academic context through bibliometric analysis.Practitioner/Policy implication: These findings are beneficial for academic researchers and industry practitioners as they aid their understanding of the development of Good Corporate Governance research and Islamic Social Reporting, identify the underlying context, and assist in the development of a coherent concept.Research limitation/Implication: This research is also expected to expand the sub-themes related to the implementation and development of Islamic Social Reporting and Good Corporate Governance, where the number of themes has not been widely studied from 2010 to 2023.